The diffusion of CSR initiatives among SMEs in industrial clusters: some findings from Italian experiences. (1st January 2012) - Testa, Francesco; Battaglia, Massimo; Bianchi, Lara
This paper shows the results of a survey carried out in two Tuscan industrial clusters and aims at analysing the adoption of corporate social responsibility (CSR) initiatives by local small- and medium-size enterprises (SMEs) in favour of employees, suppliers and consumers. In particular, we have analysed both the role of local stakeholders in stimulating the different initiatives and the issues that SMEs consider relevant for their business strategies. This study represents an innovative contribution to the research concerning the relationship between SMEs and CSR, and better defines the role played by the connections existing among local actors involved in an industrial cluster (in order to stimulate and promote CSR). Finally, the paper evaluates the types of correlations existing between the adoption of CSR initiatives and economic performance.